Toename van het aantal dakloze vrouwen in Brussel: een nader te onderzoeken evolutie - Marjorie Lelubre (Brussels Studies)
The issue of the “feminisation” of homelessness as presented in public discourse over the past several years must be questioned. In order to do so, this analysis examines data regarding the use of two key operators in the Brussels sector – the night shelter Pierre d'Angle and the SAMU social – along with statistics centralised by La Strada. Although the hypothesis of an increase may appear to be well-founded in terms of absolute numbers, it is much less clear in relative terms. While the number of homeless women has increased in certain services, this growth is above all part of a general increase in the homeless population.Beyond the figures, the article is aimed at a better understanding of the particularities of the female residential experience, which is marked by greater use of an informal network and long-term housing structures. The categorisation of homeless people is also questioned. Finally, the effects and impacts of the image of women on the support they receive within the institutional network are discussed.